THE ROLE OF LINGUISTIC RESEARCH IN THE DEVELOPMENT OF PILGRIMAGE TOURISM (Journal of Universal Science Research, 2025)
This article examines the role of linguistic research in pilgrimage tourism, focusing on how language enhances communication, preserves cultural heritage, and enriches pilgrims' experiences. It discusses the impact of multilingual signage and informational materials on accessibility at pilgrimage sites. Additionally, the study highlights the importance of accurately translating and preserving indigenous terminologies to maintain cultural authenticity. The analysis also considers the linguistic features of pilgrimage advertising and the necessity for culturally sensitive promotional strategies. By integrating linguistic insights, the article advocates for improved communication strategies and the preservation of cultural heritage to enhance the spiritual journey of pilgrims.